Trend Micro: Unseen Threats, Imminent Losses: 2018 Midyear Security Roundup. Issue 9 (September 2018) - Unknown
Abstract : Security specialists are going to have to look harder to see the problems on their networks, says Trend Micro in its latest report. Vulnerabilities and exploits are lurking in unexpected places and many of our customary defences are unable to pick them up.